PROMOTING AWARENESS OF TEACHING COLLOCATIONS TECHNIQUES TO BEGINNERS (ADJECTIVE-NOUN COLLOCATIONS) - Mohammed Alfahadi, Abdulrahman; Ahmed Zohairy, Said; Mohammed Momani, Mowaffaq; H. Wahby, Mansour (European Scientific Journal, ESJ, 2014)
Since the ELT career is updating itself on daily basis, teachers shoulddevelop their teaching techniques to cope with modern teachingmethodology. It is essential to experiment theories and modify them to suitvarious teaching environments. Teaching collocations has become a toppriority in language teaching. Therefore, this paper discusses the issue ofteaching collocations for beginners. Although a lot of teachers might notagree on teaching collocations before upper intermediate-level, this studyclaims that exposing low-level learners (especially, beginners) to languagechunks rather than individual words enhances their abilities in writing andspeaking (communicative power). Learners may know many individualwords which they can‘t use, along with their grammatical knowledge, butthey lack the ability to use those words in a range of collocations which packmore meaning into what they say or write. In addition, learning collocationswas found also beneficial in developing learners’ skills such as criticalthinking and autonomous learning.